Measurement of electrons from charm and beauty-hadron decays in p-Pb collisions at 5.02 TeV with ALICE at the LHC. (April 2015) - Wagner, Jan
Abstract: The p T -differential production cross section of electrons from heavy-flavour hadron decays in the rapidity range -1.06 < y cms < 0.14 in p-Pb collisions at = 5.02 TeV has been measured with ALICE. The cross section of electrons from beauty-hadron decays, isolated based on their larger average displacement from the interaction vertex, is presented as well as the nuclear modification factor R pPb of heavy-flavour and beauty-hadron decay electrons. Theoretical predictions including the effects due to the nuclear modification of the parton distribution functions are discussed with the results.